2009
DOI: 10.1002/pds.1803
|View full text |Cite
|
Sign up to set email alerts
|

What can primary care prescribing data tell us about individual adherence to long‐term medication?—comparison to pharmacy dispensing data

Abstract: There is potential for general practices to identify substantial levels of long-term medication adherence problems through their electronic prescribing records. Significant further adherence problems could be detected if an e-pharmacy network allowed practices to match dispensing against prescriptions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 20 publications
3
40
0
Order By: Relevance
“…Another limitation, which applies to any secondary database analysis, includes measuring 426 adherence using secondary databases. This has been validated with other methods of 427 adherence measurement such as electronic devices, patients' self-reports and pill counts 428 [52,53], and no substantial differences between dispensing and prescribing datasets were 429 found [54]. Given the different methods to measure medication adherence using secondary 430 databases, it could be argued that each method may produce different results.…”
Section: Strengths and Limitations 365mentioning
confidence: 96%
“…Another limitation, which applies to any secondary database analysis, includes measuring 426 adherence using secondary databases. This has been validated with other methods of 427 adherence measurement such as electronic devices, patients' self-reports and pill counts 428 [52,53], and no substantial differences between dispensing and prescribing datasets were 429 found [54]. Given the different methods to measure medication adherence using secondary 430 databases, it could be argued that each method may produce different results.…”
Section: Strengths and Limitations 365mentioning
confidence: 96%
“…Visualizations of individual patterns have been implemented as part of EMR software in some clinical decision support systems (CDSS) [23] although others include only numeric adherence estimates [24], and visualizations are rarely integrated in EHD adherence research [25]. To address this issue, AdhereR includes interactive visualizations of individual medication histories and plotting of multiple histories.…”
Section: Introductionmentioning
confidence: 99%
“…Some authors found that gaps between 8 and 19 days were highly predictive of discontinuation. Using electronic prescribing records, general practices can identify substantial levels of long-term medication compliance issues 14 .…”
Section: Discussionmentioning
confidence: 99%